Effects of P301L-TAU on post-translational modifications of microtubules in human iPSC-derived cortical neurons and TAU transgenic mice - Mohamed Aghyad Al Kabbani; Christoph Köhler; Hans Zempel (Neural Regeneration Research, 2025)
TAU is a microtubule-associated protein that promotes microtubule assembly and stability in the axon. TAU is missorted and aggregated in an array of diseases known as tauopathies. Microtubules are essential for neuronal function and regulated via a complex set of post-translational modifications, changes of which affect microtubule stability and dynamics, microtubule interaction with other proteins and cellular structures, and mediate recruitment of microtubule-severing enzymes. As impairment of microtubule dynamics causes neuronal dysfunction, we hypothesize cognitive impairment in human disease to be impacted by impairment of microtubule dynamics. We therefore aimed to study the effects of a disease-causing mutation of TAU (P301L) on the levels and localization of microtubule post-translational modifications indicative of microtubule stability and dynamics, to assess whether P301L-TAU causes stability-changing modifications to microtubules. To investigate TAU localization, phosphorylation, and effects on tubulin post-translational modifications, we expressed wild-type or P301L-TAU in human MAPT-KO induced pluripotent stem cell-derived neurons (iNeurons) and studied TAU in neurons in the hippocampus of mice transgenic for human P301L-TAU (pR5 mice). Human neurons expressing the longest TAU isoform (2N4R) with the P301L mutation showed increased TAU phosphorylation at the AT8, but not the p-Ser-262 epitope, and increased polyglutamylation and acetylation of microtubules compared with endogenous TAU-expressing neurons. P301L-TAU showed pronounced somatodendritic presence, but also successful axonal enrichment and a similar axodendritic distribution comparable to exogenously expressed 2N4R-wildtype-TAU. P301L-TAU-expressing hippocampal neurons in transgenic mice showed prominent missorting and tauopathy-typical AT8-phosphorylation of TAU and increased polyglutamylation, but reduced acetylation, of microtubules compared with non-transgenic littermates. In sum, P301L-TAU results in changes in microtubule PTMs, suggestive of impairment of microtubule stability. This is accompanied by missorting and aggregation of TAU in mice but not in iNeurons. Microtubule PTMs/impairment may be of key importance in tauopathies.